1992
DOI: 10.3109/00365599209181227
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Metastases in 102 Patients Evaluated Before Surgery for Renal Cell Carcinoma

Abstract: During a 3-year period a consecutive series of 102 patients were treated for renal cell carcinoma at one urological unit. Thirty-three patients (32.4%) had metastatic spread, but bone metastases were found in six patients only, i.e. 5.9% of the whole series and 18.2% of the patients with metastases preoperatively. The bone metastases had in all six patients given local symptoms first indicating radiography, and thereafter radionuclide scintigraphy of the entire skeleton. Bone scintigraphy performed merely by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 5 publications
2
10
0
6
Order By: Relevance
“…Our findings are thus in agreement with Henriksson et al, 9 who found a low diagnostic value of SAP for the identification of patients with bone metastases and concluded that early diagnosis of a skeletal metastasis is best achieved by careful physical examination of the patient as well as careful history-taking. At many institutions, wholebody BS is still considered part of the staging assessment, at least for preselected patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are thus in agreement with Henriksson et al, 9 who found a low diagnostic value of SAP for the identification of patients with bone metastases and concluded that early diagnosis of a skeletal metastasis is best achieved by careful physical examination of the patient as well as careful history-taking. At many institutions, wholebody BS is still considered part of the staging assessment, at least for preselected patients.…”
Section: Discussionsupporting
confidence: 93%
“…Almost 30% of patients with RCC will progress to distant metastases during postoperative follow-up [1,2]. Thus, more than 50% of all patients with RCC develop metastases in the course of their disease and require individual treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…In approximately 30% of patients with renal cell carcinoma (RCC), the primary diagnosis is made at a stage of metastasized cancer [1]. Moreover, of initially localized tumors, 30–50% progress to distant metastases [2, 3].…”
Section: Introductionmentioning
confidence: 99%